Carbon and nutrient fluxes through litterfall at four succession stages of Caatinga dry forest in Northeastern Brazil - Moura, Patrícia M; Althoff, Tiago D; Oliveira, Renann A; Souto, Jacob S; Souto, Patrícia C; Menezes, Rômulo S. C; Sampaio, Everardo V. S. B (Nutrient cycling in agroecosystems, 2016)
Knowledge about litterfall and its nutrient fluxes is important for understanding ecosystem dynamics, especially in regards to vegetation at different succession stages. Regenerating vegetation represents a large proportion of tropical forests, such as the caatinga dry forest in NE Brazil, which is heavily used for fuel wood and slash-and-burn agriculture. In the present study we measured litterfall for 2 years in four regeneration stages of caatinga: recently abandoned pasture, 15-, 37-, and 57-years (mature caatinga) of regeneration. The lowest litter C fluxes were observed in pasture sites but the highest fluxes occurred in the intermediate regeneration stages (15 and 37 years of regeneration) than in the mature caatinga. The 15-year site had the highest concentrations and the greatest fluxes of nitrogen and phosphorus. Nutrient concentrations in litter were in the range of those found in other dry forests, but the fluxes were lower. The high N:P concentration ratios indicate that P is a limiting nutrient in this ecosystem. The proportion of total litterfall C fluxes relative to total C stocks in the ecosystem decreased consistently with succession age, but annual net C accumulation in the ecosystem increased with succession age. The results suggest that litterfall in earlier regeneration stages is more strongly affected by rainfall variation than mature vegetation, but these patterns need to be further investigated for longer periods. This higher stability of mature ecosystems could be important in face of the expected higher climatic variability in the future.